2014
DOI: 10.1007/s12630-014-0184-z
|View full text |Cite
|
Sign up to set email alerts
|

Off-label use of recombinant activated factor VII in surgical and non-surgical patients at 16 Canadian hospitals from 2007 to 2010 (Canadian Registry Report)

Abstract: The off-label use of rFVIIa in Canada remains stable. Since severity of bleeding is prognostically important, the benefits of rapidly gaining control of bleeding that is non-responsive to conventional therapies may at times warrant the use of potent hemostatic drugs with established risk profiles, such as rFVIIa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…However, an improved outcome was found with the off-label use of rFVIIa in cases with uncontrollable coagulopathic bleeding unresponsive to conventional therapy [ 16 21 ] and this has been supported by two major studies. In a recent multicenter study at 16 Canadian hospitals for which 1378 cases received rFVIIa, transfusion requirements were substantially decreased after the administration of rFVIIa and the rate of adverse events was strongly related to the severity of bleeding [ 10 ]. The severity of bleeding undermined any potential risks related to thrombotic events and authors felt that major bleeding was the main determinant of outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an improved outcome was found with the off-label use of rFVIIa in cases with uncontrollable coagulopathic bleeding unresponsive to conventional therapy [ 16 21 ] and this has been supported by two major studies. In a recent multicenter study at 16 Canadian hospitals for which 1378 cases received rFVIIa, transfusion requirements were substantially decreased after the administration of rFVIIa and the rate of adverse events was strongly related to the severity of bleeding [ 10 ]. The severity of bleeding undermined any potential risks related to thrombotic events and authors felt that major bleeding was the main determinant of outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, rFVIIa has been increasingly used in a variety of off-label indications including cardiac surgery [ 3 , 4 ], liver transplantation [ 5 ], trauma [ 6 ], and extracorporeal membrane oxygenation [ 7 ]. Although the use of rFVIIa in uncontrollable bleeding is not associated with mortality benefit [ 8 , 9 ], several studies have shown an improved outcome [ 10 , 11 ]. Nonetheless, concerns have been raised regarding the increased risk of thrombotic events [ 12 14 ], the main argument for limiting rFVIIa off-label use.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, the use of rFVIIa has been also extended to those cases in which patients presented thrombocytopenia, platelet function abnormalities and warfarin over-anticoagulation. 7 Moreover, it has been used in various conditions such as adult and pediatric cardiovascular surgery, obstetrical hemorrhage, trauma, intracranial hemorrhage, gastrointestinal bleeding, urologic surgery, and transplantation. 6,8,9 It is not associated with the risk of blood-transmitted diseases, as a recombinant product is not derived from human or animal plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Although not approved by FDA for control of postsurgery bleeding it has been used after obstetric and cardiac surgery to control refractory hemorrhage. [ 98 99 100 101 102 103 ] In addition to its, therapeutic role rFVIIa has also been used as a prophylactic agent to prevent excessive blood loss. [ 104 ] Before administering rFVIIa, the platelet count should be fair (50,000/µl) and any consumption coagulopathy should be ruled out.…”
Section: Topical Hemostatic Agentsmentioning
confidence: 99%